Effect of dynamic blocking of dislocations by interstitial atoms on mechanical properties of metals and alloys - Shirokov, V.V.; Pavlyna, O.V.; Shirokov, O.V. (Functional Materials, 2004)
According to the experimentally approved theoretical calculations it has been estab -lished, that under some temperature speed conditions of tension of transition metals and their alloys, a dynamic interaction of the interstitial atoms with dislocations takes place. This effect leads to strengthening of this materils. The temperature of dynamic interaction for hydrogen, oxygen, carbon in iron of two modifications and metals of V-A group are calculated. Согласно теоретическим расчётам, подтвержденным экспериментально, показано, что при определенных температурно-скоростных условиях растяжения переходных металлов и сплавов на их основе происходит динамическое взаимодейстие атомов внедрения с дислокациями, которое приводит к их упрочнению. Рассчитаны температуры динамического взаимодействия для водорода, азота, кислорода и углерода в железе двух модификаций и металлах V-A группы. Згідно теоретичних розрахунків, підтверджених експериментально, показано, що за певних температурно-швидкісних умов розтягування перехідних металів і сплавів на їх основі відбувається динамічна взаємодія атомів упровадження з дислокаціями, яке призводить до їх зміцнення. Розраховано температури динамічної взаємодії для водню, азоту, кисню, і вуглецю в залізі двох модифікацій і металах V-A групи.